Using code-switching as the teaching strategy in classroom for low English proficiency learners - Herawati Herawati; Siti Sarah Fitriani (Universitas Syiah Kuala, 2021)
This qualitative study is aimed to find the function of teachers’ code-switching (CS) to support low proficiency learners in learning English and to determine the benefits of CS practiced by the teachers in the EFL learning. The data of this study were obtained from two English teachers at Junior Islamic Boarding School of Darul Ihsan, Aceh Besar. The observation sheet and questionnaire were used to collect the data. Two English classes were observed in two sessions respectively. All of the conversation in the classroom was recorded and the code-switching parts were then transcribed and analyzed. The results showed that the teachers used CS for clarification, explaining difficult grammatical terms, building connections between teacher and students, quoting specific terms that is not available in English, adding specification, repeating message which previously said in English, explaining message qualification, and emphasizing a particular issue. The results of the questionnaires showed several benefits of implementing CS for students, such as enjoying communication during learning activities, feeling satisfied and comfortable in the learning situation, feeling less tense and rigid, focusing more on the lesson, improving their ability to understand new words, and helping them understand difficult concepts and grammar in English.